Guía de diagnóstico y control para intoxicación por nitratos y nitritos en ganado bovino (2021)
Nitrate poisoning in cattle generates important economic losses in cattle, this happens when after a period of drought the rains arrive, there is when nitrates accumulate in the plants, then the animal (cattle) consumes the plants with high content of nitrates, which are transformed in the gastrointestinal tract, reach the bloodstream and intoxication is generated there.